EFFECTIVENESS OF DIRECT INSTRUCTION FOR LEARNING MODELS IMPROVING BATIK SKILLS IN BASIC SCHOOL STUDENTS IN SANGGAR BATIK CIKADU - Minhatul Ma’arif; Muhardila Fauziah; Rizal Fauzi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This research was driven by the low batik making skills of elementary school students who take part in the educational tourism (edutourism) activities in Cultural Arts and Skills (SBK) in the Sanggar Batik Cikadu Tanjung Lesung. This research aims to improve the learning process of batik class at Sanggar Batik Cikadu Tanjung Lesung in improving batik skills in elementary school students in Pandeglang Regency. This study uses a classroom action research (CAR) in a batik class with a total of 50 students in grade 5 (five) elementary schools coming from 5 (five) elementary schools in the Pandeglang Regency. Each school sent 10 students to take part in this batik class. The data used in the form of instructor and student activities in the process of batik using a direct instructor model and the results of batik skills according to levels in Bloom's taxonomy. The results were obtained through 2 (two) cycles, each cycle consisting of 2 (two) meetings with a time allocation of 2 x 30 minutes. Based on data analysis the results of the study found that there was a significant increase in each cycle. The first cycle instructor activity was only 69.5%, the second cycle increased significantly to 82%. Furthermore, in student activities, the first cycle only 33.5%, in the second cycle to 80%. Likewise in the students' batik making skills, each cycle changes. In the first meeting at the first cycle, it was 28.75%, then in the second meeting it increased to 59.75%. In cycle II the first meeting increased again by 76.75% while at the second meeting increased quite dramatically by 84.75%. So it can be concluded that the application of the direct instruction model in the batik class in Sanggar Batik Cikadu for class 5 (five) is an effective basis for improving batik skills.